Asymptotic Representations for the Solutions of One Class of Nonlinear Differential Equations of the Second Order - Shlepakov, O. R.; Шлепаков, О. Р.; Шлепаков, О. Р. (Institute of Mathematics, NAS of Ukraine, 2015)
We establish asymptotic representations for the solutions of one class of nonlinear differential equations of the second order with rapidly and regularly varying nonlinearities.